2002
DOI: 10.1002/ptr.892
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of the methanol fraction of Pluchea indica root extract

Abstract: Studies were carried out to evaluate the influence of the methanol fraction of Pluchea indica Less root extract (PIRE), the dual inhibitors (BW 755C and phenidone) and vitamin on both in vivo and in vitro free radical-scavenging activities, CCl(4)-induced lipid peroxidation and the metabolism of arachidonic acid by lipoxygenase. PIRE produced significant antiinflammatory activity against glucose oxidase-induced paw oedema (in vivo), inhibited hydroxyl radical and superoxide generation, lysis of erythrocytes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…Sudarman et al (2011) applied Pluchea indica in broilers feeding and observed over 8% decrease in cholesterol content in meat. Strong antioxidative properties of P. indica have been widely known and described by Sen et al (2002). Sudarman et al (2011) suppose that it is thanks to these properties that they obtained such an effect.…”
Section: Resultsmentioning
confidence: 97%
“…Sudarman et al (2011) applied Pluchea indica in broilers feeding and observed over 8% decrease in cholesterol content in meat. Strong antioxidative properties of P. indica have been widely known and described by Sen et al (2002). Sudarman et al (2011) suppose that it is thanks to these properties that they obtained such an effect.…”
Section: Resultsmentioning
confidence: 97%
“…18,21 When methanol extract of Limnophila heterophylla and vitamin E were additional to the reaction mixture, they removed hydroxyl group radicals and prevented the degradation of 2-deoxy-2-sugar as mentioned higher than the IC 50 observed values of each plant extract and Vitamin E were analogous to the reportable values of Sen et al,. 35 Total anti oxidant activity of Limnophila heterophylla was determined by ABTS radical cation decolourization assay 23 by measuring the reduction of the radical cation as the percentage inhibition. Limnophila heterophylla exhibited effective antioxidant activity at all doses.…”
Section: Discussionmentioning
confidence: 99%
“…Root extract has also been evaluated for (Sen et al, 1991), antiulcer (Sen et al, 1993), and neuropharmacological (Thongpraditchote Kartick Chandra Pramanik and Tapan Kumar Chatterjee et al, 1996) actions. The hypoglycemic and antihyperglycemic activity of leaf extract of P. indica and the antioxidant activity (Sen et al, 2002) of roots of P. indica Less. have been already documented.…”
Section: Introductionmentioning
confidence: 99%